The Limits of Entrapment: The Negotiations on EU Reduction Targets, 2007–111. (5th August 2013) - Skovgaard, Jakob
Abstract In 2007, the EU decided to cut greenhouse gas emissions by 20/30 per cent, something which was considered a proof of the EU's willingness to take on high targets independently of others. In the period 2009–11, the EU was debating but could not reach an agreement on stepping up to a 30 per cent reduction target. This raises the question: why did the EU go from being capable of adopting high targets independently of others to being incapable of agreeing whether it should increase its mitigation effort? It is argued that whereas actors sceptical of a high target could be rhetorically entrapped in 2007, such entrapment was impossible in the 2009–11 period. The lack of entrapment can be explained in terms of changes in the international and socio‐economic contexts, which led to changes in the policy processes and the normative environment, which again made effective entrapment impossible.